CAN TRANSPARENCY AND PROFESSIONALISM MODERATE THE INFLUENCE OF TRUST AND ZAKAT LITERACY ON INTEREST IN PAYING ZAKAT AT BAZNAS REMBANG? (ZISWAF: Jurnal Zakat dan Wakaf, 2024)
The purpose of this study is to empirically examine the influence of trust and zakat literacy on the public's interest in paying zakat in BAZNAS Rembang, with professionalism and transparency as moderating variables. This research employs a quantitative approach with explanatory research design. The techniques used include observation, interviews, and direct questionnaires at the research location. The sample for this study consists of 152 respondents. Data analysis is conducted using SEM-PLS analysis. The results show that trust and zakat literacy positively and significantly impact the interest in paying zakat. Professionalism can moderate (strengthen) the influence of trust and zakat literacy on the public's interest in paying zakat, with professionalism as a moderating variable at BAZNAS Rembang. It means the more professional Amil, the level of trust and zakat literacy among Muslims in paying zakat will be stronger. Transparency can also moderate (strengthen) the influence of trust and zakat literacy on the public's interest in paying zakat, with professionalism as a moderating variable at BAZNAS Rembang. This implies that better transparency in zakat institutions will strengthen the level of trust and zakat literacy, encouraging individuals to pay zakat to BAZNAS Rembang